Jiedu Huoxue decoction improves inflammation in rat type III prostatitis: The importance of the NF‐κB signalling pathway. (6th February 2019) - Yan, Zhangren; Huang, Chunhua; Huang, Gang; Wu, Yunbo; Wang, Jiangang; Yi, Jun; Mao, Wenli; Wang, Wanchun
Abstract: This study aimed to investigate the mechanism of Jiedu Huoxue decoction (JDHXD) in type III prostatitis based on the NF‐κB signalling pathway. Twenty‐six Sprague–Dawley male rats were divided into blank control, model, positive (Prostate Plus), low‐dose JDHXD, medium‐dose JDHXD and high‐dose JDHXD groups. Type III prostatitis rat model was established and confirmed with HE staining. NF‐кB P50 and NF‐κB P65 expression was detected with immunohistochemistry. NF‐κB mRNA expression was detected with qRT‐PCR. Protein expression of NF‐κB and its inhibitor Iκ‐Bα was detected with Western blot. Compared to the model group, a decrease in glandular hyperplasia and inflammation, and in NF‐кB P50 and NF‐κB P65 expression in the medium‐ and high‐dose JDHXD groups was observed. NF‐κB mRNA expression was significantly increased in the model group compared to control ( p < 0.05), and significantly decreased in the JDHXD treatment groups compared to model group ( p < 0.05). Protein expression of NF‐κB was significantly increased in the model and low‐dose JDHXD groups compared to control( p < 0.05), and significantly decreased in the medium‐ and high‐dose JDHXD groups compared to model group ( p < 0.05). Protein expression of Iκ‐Bα was vice versa. JDHXD could be a potential treatment for type III prostatitis via its regulation of NF‐κB and Iκ‐Bα expression.